(untitled) (Journal of Bangladesh Academy of Sciences, 2012)
A total of 21 isolates were included randomly on the basis of their initial identification by the appearance of metallic sheen and from the biochemical traits to detect virulent markers of diarrhoeagenic E. Coli isolated from surface water. The antibiotic susceptibility pattern of the isolates were determined against six most commonly used antibiotics. About 52% of the isolates showed resistance to at least one of the antibiotics. About 38% of the isolates were resistant to more than one antibiotics. However, all the isolates were sensitive to gentamicin (CN). Among the 21 isolates, a total of 5 randomly selected isolates were examined for the detection of virulent genes (elt, est and stx) by PCR based method. Among the 5 tested isolates, 3 harbored the gene stx encoding Shiga toxin (Stx) and 2 to elt encoding heat-labile enterotoxin (LT). None of the isolates contained est encoding heat-stable enterotoxin (ST). Data revealed that as the virulent marker genes were detected, diarrhoeagenic E. coli strains present in the surface water would become a major public health concern. DOI: http://dx.doi.org/10.3329/jbas.v36i1.10927 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 1, 109-121, 2012